METODA VOLUME HINGGA DENGAN JALA TAK-TERSTRUKTUR UNTUK MENSIMULASIKAN PERLUASAN PULAU AKIBAT DEPOSISI SEDIMEN - Caniago, Zulbahrum (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Method finite volume (FVM) has been used for resolving non-linear equations that model the sedimentary cases where the formation and expansion of the island in the estuary. Non-linear equation as the formula is the equation of hydrodynamics transport of sediment. In the completion of the transport equation is done by using the space discretization technique unstructured triangular elements. Data generated numerical solutions of sediment deposition rate distribution spatially and temporally as information dynamics formation and expansion of the island due to sedimentation in the estuary, in this case is the phenomenon of islands in the estuary Ekortikus Banyuasin (MSB) South -Sumatera. Accretion of sediment case raises broad impact on narrowing the island at the mouth thereby affecting the capacity of the distribution of the flow. Two rivers flow into estuaries, rivers Banyuasin and Lalan as well as the influence of the tidal wave is a factor that plays an important role in distributing the sedimentation of the estuary. The results showed that the formation and expansion of the island occurred in the flow stagnation zone and the curvature due to the shear stress in the vertical direction between two streams. Study of the formation mechanism of the island is also strengthened by giving treatment to the system by changing the flow rate of the river and put the potential barrier at the mouth. Keywords: Simulation, Sedimentation, Finite Volume Method, Potensial Barrier, Estuary.